ROLA LISTÓW W K SZTAŁTOWANIU WIZERUNKU „APOSTOŁA WSCHODU” – ELEMENTY AUTOBIOGRAFICZNE W ŁACIŃSKIEJ KORESPONDENCJI FRANCISZK A KSAWEREGO - Miazek-Męczyńska, Monika (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
This paper presents the letters of Francis Xavier, Jesuit missionary, called “an Apostle of the Far East”, as a kind of episolographical autobiography. In a short time after publication of his letters, the missionary work of Francis Xavier, which he himself describes in detail, became a model for all later activities of the Society of Jesus in Asia and all New World.